Phylotranscriptomics Illuminates the Placement of Whole Genome Duplications and Gene Retention in Ferns - Pelosi, Jessie A.; Kim, Emily H.; Barbazuk, W. Brad; Sessa, Emily B. (Frontiers in Plant Science, 2022)
Ferns are the second largest clade of vascular plants with over 10,000 species, yet the generation of genomic resources for the group has lagged behind other major clades of plants. Transcriptomic data have proven to be a powerful tool to assess phylogenetic relationships, using thousands of markers that are largely conserved across the genome, and without the need to sequence entire genomes. We assembled the largest nuclear phylogenetic dataset for ferns to date, including 2884 single-copy nuclear loci from 247 transcriptomes (242 ferns, 5 outgroups), and investigated phylogenetic relationships across the fern tree, the placement of whole genome duplications (WGDs), and gene retention patterns following WGDs. We generated a well-supported phylogeny of ferns and identified several regions of the fern phylogeny that demonstrate high levels of gene tree–species tree conflict, which largely correspond to areas of the phylogeny that have been difficult to resolve. Using a combination of approaches, we identified 27 WGDs across the phylogeny, including 18 large-scale events (involving more than one sampled taxon) and 9 small-scale events (involving only one sampled taxon). Most inferred WGDs occur within single lineages (e.g., orders, families) rather than on the backbone of the phylogeny, although two inferred events are shared by leptosporangiate ferns (excluding Osmundales) and Polypodiales (excluding Lindsaeineae and Saccolmatineae), clades which correspond to the majority of fern diversity. We further examined how retained duplicates following WGDs compared across independent events and found that functions of retained genes were largely convergent, with processes involved in binding, responses to stimuli, and certain organelles over-represented in paralogs while processes involved in transport, organelles derived from endosymbiotic events, and signaling were under-represented. To date, our study is the most comprehensive investigation of the nuclear fern phylogeny, though several avenues for future research remain unexplored.